Effectiveness of sanitation policy instruments in Mavoko Municipality of Machakos County, Kenya - Mutua, Juliana Kamanthe Muia; Agwata, Jones F.; Anyango, Stephen (Cogent, 2017)
Improved sanitation leads to better environmental quality however threatened environments, population densities and inadequate finances are some of the challenges facing proper sanitation management. This paper sought to establish the effectiveness of policy, legal and institutional frameworks on promotion of sanitation management in Mavoko Municipality. Resident’s awareness and compliance with policy instruments, role and responsibilities of Mavoko Municipality Residents and Service Providers and Political Champions were used to gauge the effectiveness of these policy instruments. Mavoko Municipality has low sewer network coverage with a deficit of 86% in sewerage treatment capacity as its existing sewerage treatment capacity stands at 192,000 m3 against a required capacity of 1,407,000 m3 . The study site covered the urbanizing areas within the Municipality. A cross-sectional study design was chosen and both primary and secondary data were collected. 385 house hold respondents were interviewed. Simple random and purposive sampling methods were used to administer questionnaires to standalone houses and comprehensive housing schemes. Key informant interviews with County and National Officials mandated with sanitation management related services were conducted using structured forms and interview guides. Findings indicate that existing policies and legal frameworks are not effective as they play little role in influencing policy for the promotion of appropriate sanitation management approaches. Political championing was negligible whilst County Government performed poorly in sanitation management. Commitment to providing sanitation services and building capacities and strengths of Service Providers and emerging Residential Neighbourhood Association is recommended to promote good practices in sanitation and environmental management.
Keywords: Compliance; Mavoko; Policy; Legal and institutional frameworks; Political champion; Sanitation management